The “Tough on Crime” Competition: a Network Approach to Understanding the Social Mechanisms Leading to Federal Crime Control Legislation in the United States from 1973–2014 - Shjarback, John A. (American journal of criminal justice, 2018)
The increase in punitive sentiment in America over the last four decades is frequently attributed to changes in criminal justice policies and programs. While scholars have studied the impact of legislation and policy on justice system outcomes, less attention has focused on the role of political actors in legislative bodies who are largely responsible for enacting criminal justice legislation. The current study addresses this gap by examining the social organization of federal crime control policy in the U.S. Congress over a forty-two year period (1973–2014). Drawing from research on social network mechanisms, we examine whether crime control legislation was more politically attractive relative to other legislative topics, and whether Democrats and Republicans pursue these policies by working together or competing against each other. Our results provide novel insight into the mechanisms that contributed to the punitive movement at the federal level.